Data Analysis of Fiscal Expenditure and GDP Based on Financial Budget Performance Evaluation Indicators - Jianhui Zhang (Discrete Dynamics in Nature and Society)
The proportion of fiscal revenue in GDP and the multiplier of fiscal expenditure are important economic benefit indicators in the framework of a common index system for budget performance evaluation. The correlation between fiscal expenditure and GDP constitutes an important indicator to measure fiscal scale, and the scale and structure of fiscal expenditure play a guiding role in the distribution of social renewable production. At the same time, there is a certain mutual promotion between the two. This paper selects the data of China’s GDP and fiscal expenditure from 1998 to 2019, analyzes the trend, respectively, and then carries out correlation and regression analysis. On this basis, it scientifically calculates the scale of China’s GDP in the next five years and puts forward suggestions to optimize fiscal expenditure.